MECHANISMS AND STRATEGIC DIRECTIONS OF THE DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP IN UKRAINE - BRAUNAGEL, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the current state of social entrepreneurship in Ukraine, its role in addressing socio-economic challenges, and the primary obstacles hindering its development. Social enterprises serve as a crucial mechanism for solving pressing societal issues by combining commercial activities with social impact. However, their growth is significantly constrained by the absence of a clear legislative framework, limited financial resources, low public awareness, and difficulties in integrating into the market economy. A detailed analysis of these challenges is provided, highlighting the lack of regulatory recognition for social enterprises, which limits their access to tax benefits, financial support programs, and government incentives. Additionally, the financial sustainability of social enterprises remains a pressing issue due to the difficulties in securing initial investments, obtaining bank loans, and attracting private investors. The study emphasizes the necessity of introducing new financial mechanisms, including grant programs, preferential lending, social investment funds, and crowdfunding platforms to enhance the financial viability of social businesses. Another critical aspect covered in the article is the insufficient awareness and understanding of social entrepreneurship among the general public, potential entrepreneurs, and consumers. This factor significantly affects market demand and the scalability of social enterprises. Strategies for overcoming these barriers include the implementation of national information campaigns, the organization of business forums, exhibitions, and educational initiatives to promote social entrepreneurship. Moreover, the introduction of labeling systems for social enterprise products is proposed to help consumers identify goods and services that generate social value. The article also explores strategic directions for stimulating the development of social entrepreneurship in Ukraine. The recommendations include the development of a comprehensive legislative framework, the creation of tax incentives, the expansion of financial support mechanisms, and the promotion of cross-sectoral collaboration between the government, private sector, and civil society. In conclusion, the research highlights the need for an integrated approach to fostering social entrepreneurship as a vital instrument for sustainable development.